Do Homeschooled Students Lack Opportunities to Acquire Cultural Capital? Evidence from a Nationally Representative Survey of American Households. Issue 3 (27th May 2019) - Hamlin, Daniel
ABSTRACT: Experiences at school may create valuable opportunities for children to acquire cultural capital. One concern for homeschooled children is that they may be deprived of these opportunities. However, homeschool families may enable opportunities for their children to acquire cultural capital through participation in activities outside of formal instructional time. This study investigates this possibility by comparing cultural and family activities between homeschooled students and their public school peers. The analyses use data from a nationally representative survey (National Household Education Survey, 2016) containing a substantial number of respondents who homeschool their children ( n = 552). Descriptive results indicated that formal instruction in music, arts, literature, and foreign language is lacking in nearly 40% of homeschool households. Yet, relative to public school families, homeschool families report statistically higher participation in cultural and family activities. While patterns observed in this study are only descriptive, overall evidence suggests that homeschool families may provide opportunities for their children to acquire cultural capital through greater participation in cultural and family activities.